Recycled carbon fiber bundle composition and method for producing same

JP7640110B2Active Publication Date: 2025-03-05FUJI DESIGN CO LTD
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
JP2022534359
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2021-05-28
Filing Date
2022-03-18
Publication Date
2025-03-05
Estimated Expiration
2042-03-18

AI Technical Summary

Benefits of technology

【0012】 本発明によれば、炭素繊維強化型硬化性樹脂成形体から取り出されたリサイクル炭素繊維収束体を、該収束体に含まれる炭素繊維との間で化学的親和性を示す化学的官能基を有する表面改質剤と混合した組成物としているため、リサイクル炭素繊維収束体を再利用するためにマトリックス樹脂と混練りする作業を一層安定なものとすることができる。また、本発明のリサイクル炭素繊維収束体組成物から形成されるシートは、機械的特性が良好となる。また、本発明によれば製造された成形体の物性を一層安定なものとすることができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007640110000001
    Figure 0007640110000001
  • Figure 0007640110000002
    Figure 0007640110000002
Patent Text Reader

Abstract

The present invention addresses the problem of establishing a practical technique by which recycled tow-fiber bundles can be more stably kneaded, for reuse, together with a matrix resin and molded objects having more stable properties can be produced. The recycled-carbon-fiber bundle composition according to the present invention comprises: recycled-carbon-fiber bundles taken out of molded carbon-fiber-reinforced heat-cured resins; and a surface modifier having a second chemical functional group, which exhibits a chemical affinity for a first chemical functional group, which is present on the surface of the carbon fibers. The recycled-carbon-fiber bundles are tows of carbon fibers bundled with amorphous carbon. The recycled-carbon-fiber bundle composition contains the surface modifier in an amount of 0.1-1 mass% with respect to the whole composition, which is taken as 100 mass%. The recycled-carbon-fiber bundle composition, when examined after having been heated under the conditions of 600°C and 60 minutes, has a residual carbon content of 1-5 mass%.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a composition containing a recycled carbon fiber (hereinafter, sometimes referred to as rCF) bundle recovered from a carbon fiber reinforced thermosetting resin (hereinafter, sometimes referred to as CFRP) molding, and a method for producing the same. [Background technology]

[0002] CFRP molded products, which are made by kneading and compounding carbon fibers into a thermosetting matrix resin, have been used as structural materials that require high strength and high elasticity, such as in aerospace aircraft and racing cars, but in recent years, their applications have expanded, for example, to include thick-walled molded products such as wind turbine blades and compressed natural gas cylinders (hereafter sometimes referred to as CNG cylinders).CFRP molded products are not only used in the large products mentioned above, but are also increasingly being used as the frameworks of sporting goods such as tennis rackets, and the housings of familiar electronic devices such as laptops, tablet computers, and smartphones.

[0003] As the market for CFRP molded bodies expands, a large amount of used CFRP molded bodies and CFRP or prepreg scraps generated during trimming during manufacturing will be discarded. From the viewpoint of effective resource utilization, it is desirable to establish a rational and economical recovery technology. However, since no useful recovery technology has been established at present, most of these are simply landfilled. However, since the carbon fibers in CFRP molded bodies are conductive, there is a problem that fragments of CFRP molded bodies scattered from the landfill soil into the air can cause electrical or radio interference to nearby electrical devices or have unexpected adverse effects on the human body. It has also been pointed out that even if CFRP molded bodies are mistakenly incinerated, there is a risk of similar problems if carbon fibers are scattered during the treatment process. On the other hand, the trend toward expanding the use of CFRP molded bodies requires further production of carbon fibers, but the production of new carbon fibers requires a large amount of energy consumption, which not only increases costs but also raises environmental concerns such as increasing carbon dioxide emissions. This brings us back to our original challenge: the need to develop technology to efficiently recover carbon fibers from CFRP bodies.

[0004] Such recovery techniques are known, for example, in Patent Documents 1 and 2, and Non-Patent Document 1, which was published by the present inventors as one of the authors, and Patent Document 3, which was developed by the present inventors and published as a patent application, is also known. Patent Document 1 shows a method for treating carbon fiber reinforced plastics, in which the plastics are thermally decomposed by heat-treating the carbon fiber reinforced plastics without combustion in a gas atmosphere with an oxygen concentration in the range of 3 to 18% by volume and a temperature in the range of 300 to 600°C. Patent Document 2 describes a method for producing short carbon fibers, in which a group of carbon fibers bonded with resin are crushed into fibers in the range of 100 μm to 3 mm, classified to adjust the fiber length, and one or more of each classified product are thermally decomposed at 350 to 500°C under a decomposition gas of the crushed product. Non-Patent Document 1 discloses a method for recovering carbon fibers by placing a CFRP molded body in an infrared heating furnace, heating it to 400°C at a temperature increase rate of 50°C / min while forming an air flow with a flow rate of 0.3 m / min, and maintaining it for 120 minutes. Patent Document 3 discloses that a recycled carbon fiber bundle can be produced by heating a CFRP molded body in a temperature range of 400°C or higher and not exceeding 480°C, controlling the oxygen concentration in the atmospheric gas to 15-19% by volume in the section from when the temperature reaches 300°C to when the heating is finished, and maintaining the temperature for at least 1 hour in the section from when the temperature reaches 300°C to when it reaches 350°C, as well as maintaining the temperature in a temperature range of 400°C or higher for at least 30 minutes, in which carbon fibers with an average fiber length of 6-100 mm are bundled into a tow shape using an amorphous carbon precursor derived from a thermosetting resin, and the potential hydrogen content is 600-8000 ppm by mass. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] Japanese Patent Application Publication No. 6-99160 [Patent Document 2] Japanese Patent Application Publication No. 11-50338 [Patent Document 3] JP 2018-202810 A [Non-patent literature]

[0006] [Non-Patent Document 1] Kenji Ushigoe, Nobuyuki Komatsu, Morihiko Sugino, "Recycling of CFRP by Pyrolysis", Materials, The Japan Society for Materials Science, April 1995, Vol. 44, No. 499, pp. 428-431 Summary of the Invention [Problem to be solved by the invention]

[0007] Carbon fibers recovered by the technical means of Patent Documents 1 and 2 and Non-Patent Document 1 are obtained in a scattered state with the matrix resin constituting the CFRP molded body almost completely removed, and it was extremely difficult to obtain the fibers with an optimal length and uniformity. For example, long fibers have a cotton-like appearance in which they are entangled with each other, so it is physically difficult to knead them with virgin resin using a twin-screw extruder when reusing them as reinforcing fibers, for example, to feed them using a side feeder during the resin kneading process. Even if the difficulties were overcome and kneading was performed, they could not be efficiently and uniformly dispersed in the resin. On the other hand, short fibers have a powdery appearance and are easily scattered into the environment, often causing a fuming situation that not only worsens the working environment but also causes electrical interference in electrical equipment, and have an essential defect in that the fiber length is too short to be expected to reinforce the matrix resin. Furthermore, it is extremely difficult to classify the recovered carbon fibers to make them the same length, and if the fibers are used while they are uneven in length, the problems described above cannot be avoided. Even if the fibers could be classified, those that are too long or too short have no reuse value in the first place and must be discarded, so that the recovery technology has a very low level of completion.

[0008] In contrast to these, the technology described in Patent Document 3 allows for temperature and oxygen concentration control in the recovery process to recover carbon fibers with an average fiber length of 6 mm to 100 mm that are bundled into a tow shape using amorphous carbon precursors derived from thermosetting resins, and is therefore attracting attention as a technology for reusing and utilizing carbon fibers that has suddenly reached a practical level (a sustainable material certified by the SDGs).

[0009] As the inventors continued their research towards the practical application of this technology, they found that the CFRP molded bodies collected from the city as items to be collected, or the prepreg scraps that are their raw material, are uneven in shape and size, particularly the thickness of plate-shaped bodies. This can lead to suitability or inadequacy of the processing conditions for the CFRP molded bodies, and although there is no problem with the appearance of the collected tow-like bundles, it can cause some problems in operational stability and in the stability of the physical properties of the produced molded bodies when they are kneaded with a matrix resin for reuse.

[0010] The objective of the present invention is to establish a practical technology that can form stable strands with less fiber separation in the kneaded product of recycled carbon fiber (rCF) and resin discharged from the nozzle of a twin-screw extruder in the process of kneading recovered tow-like bundles with matrix resin for reuse, and that can achieve even greater stability and even greater stability in the physical properties of the produced molded products. [Means for solving the problem]

[0011] The present invention is as follows. [1] A recycled carbon fiber bundle composition comprising a recycled carbon fiber bundle extracted from a carbon fiber-reinforced thermosetting resin molding and a surface modifier having a chemical functional group (hereinafter referred to as a second chemical functional group) that exhibits chemical affinity with a chemical functional group (hereinafter referred to as a first chemical functional group) present on the surface of the carbon fiber, wherein the recycled carbon fiber bundle is a tow-shaped bundle of carbon fibers formed of amorphous carbon that is substantially free of resin residues, the recycled carbon fiber bundle contains 0.1 to 1 mass % of the surface modifier when the entire recycled carbon fiber bundle composition is taken as 100 mass %, and the amount of residual carbon in the recycled carbon fiber bundle composition measured after heating under conditions of 600°C for 60 minutes is 1 to 5 mass %. [2] The recycled carbon fiber bundle composition according to [1], wherein the first chemical functional group is at least one selected from a carboxyl group, an aldehyde group, and a carbonyl group, and the second chemical functional group is at least one selected from a hydroxyl group, an epoxy group, an acryloyl group, a phenyl group, an acryl group, a urethane group, a silanol group, a siloxane group, an ester group, an imide group, a nitrile group, a stearic acid group, and a maleic acid group. [3] A sheet formed from the recycled carbon fiber bundle composition according to [1] or [2]. [4] A method for producing the recycled carbon fiber bundle composition according to [1] or [2], comprising the steps of: heating a carbon fiber-reinforced thermosetting resin molding to a temperature in the range of 400°C or more and 480°C or less in a heating furnace to obtain a recycled carbon fiber bundle in which the carbon fibers are bundled into a tow shape with amorphous carbon that is substantially free of resin residues; and contacting the obtained recycled carbon fiber bundle with a liquid containing a surface modifier having a second chemical functional group that exhibits chemical affinity with a first chemical functional group present on the surface of the carbon fiber, followed by drying. In the step of obtaining the recycled carbon fiber bundle, the carbon fiber-reinforced thermosetting resin molding is heated in a temperature range of at least 300°C or more and 400°C or less under a flow of combustion gas in a heating furnace, and then maintained in an atmosphere gas having an oxygen concentration of 16 to 18% by volume at a temperature range of 400°C or more and 480°C or less for at least 30 minutes. [5] The method according to [4], wherein the average flow velocity of the combustion gas in the heating furnace is 0.1 to 10 m / sec. [6] The method according to [4] or [5], wherein the heating in the temperature range of 300°C or higher and 400°C or lower is carried out until smoke generation from the carbon fiber reinforced thermosetting resin molding stops. Effect of the Invention

[0012] According to the present invention, the recycled carbon fiber bundle extracted from the carbon fiber-reinforced curable resin molding is mixed with a surface modifier having a chemical functional group that exhibits chemical affinity with the carbon fibers contained in the bundle to form a composition, so that the operation of kneading the recycled carbon fiber bundle with a matrix resin for reuse can be made more stable. Furthermore, the sheet formed from the recycled carbon fiber bundle composition of the present invention has good mechanical properties. Furthermore, according to the present invention, the physical properties of the molded product produced can be made more stable. [Brief description of the drawings]

[0013] [Figure 1]FIG. 1 is a schematic diagram for explaining the state of a CFRP molded body when it is heat-treated, where (a) is a schematic diagram of a CFRP molded body before heat treatment, (b) is a schematic diagram showing the state when it is heat-treated at 300°C to 400°C, (c) is a schematic diagram showing the state when it is heat-treated at 400°C to 480°C, (d) is a schematic diagram showing the state when it is heat-treated at 500°C, and (e) is a schematic diagram showing the state when it is heat-treated at 600°C. [Diagram 2] (f) of Figure 2 is a schematic diagram showing an enlarged view of the surface portion surrounded by circle C of the CFRP molded body shown in (b) of Figure 1, and (g) of Figure 2 is a schematic diagram showing an enlarged view of the surface portion surrounded by circle D of the CFRP molded body shown in (d) of Figure 1. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0014] The recycled carbon fiber (rCF) bundle composition according to the present invention is a recycled carbon fiber bundle composition containing a recycled carbon fiber bundle extracted from a carbon fiber reinforced thermosetting resin (CFRP) molding and a surface modifier having a second chemical functional group that exhibits chemical affinity with a first chemical functional group present on the surface of the carbon fiber. The recycled carbon fiber bundle is characterized in that the carbon fibers are bundled into a tow shape with amorphous carbon that is substantially free of resin residues, the surface modifier is contained in an amount of 0.1 to 1 mass % when the entire recycled carbon fiber bundle composition is taken as 100 mass %, and the amount of residual carbon when the recycled carbon fiber bundle composition is heated under conditions of 600°C x 60 minutes and measured is 1 to 5 mass %.

[0015] The rCF bundle contained in the rCF bundle composition according to the present invention is taken out from a CFRP molded body. A CFRP molded body is a thermosetting resin molded body in which carbon fibers as a reinforcing material are dispersed, and from the viewpoint of carbon fibers, it can be said that the carbon fibers are bonded with a thermosetting resin. Here, examples of the thermosetting resin that serves as a binder include unsaturated polyester resin, epoxy resin, vinyl ester resin, bismaleimide resin, phenol resin, cyanate resin, and polyimide resin.

[0016] Specifically, CFRP molded articles are used in structures such as aerospace craft (e.g., rockets, artificial satellites, military aircraft, passenger aircraft, helicopter blades, etc.), racing cars, motorcycles, bicycles, railway vehicles, deep-sea exploration vessels, racing boats, measuring instruments, transport robot arms, wind turbine blades, compressed natural gas tanks (CNG tanks), golf shafts, tennis rackets, fishing rods, wheelchairs, and artificial bones, as well as the housings of portable devices such as notebook computers, tablets, and smartphones.

[0017] The rCF bundle is obtained by extracting it from such a CFRP molded body, and the carbon fibers are bundled in a tow shape with amorphous carbon. Amorphous carbon is a carbon component that is generated by heating a thermosetting resin in a heating furnace at a temperature range of at least 300°C to 400°C under the flow of combustion gas in the heating furnace, and then holding it in an atmospheric gas with an oxygen concentration of 16 to 18% by volume at a temperature range of 400°C to 480°C for at least 30 minutes. The amorphous carbon does not substantially contain any residue of a thermosetting resin. "Substantially" means that the residue of a thermosetting resin is 5% by mass or less when the entire rCF bundle is taken as 100% by mass. In addition, it is preferable that the potential hydrogen content of the rCF bundle is 8000 ppm or less.

[0018] The potential hydrogen amount can be measured using a hydrogen analyzer, such as HORIBA's "EMGA-821."

[0019] Tow-like means bundle-like. Carbon fibers bundled in a tow-like shape with amorphous carbon means that a large number of carbon fibers are arranged and bound together with amorphous carbon to form a bundle. The amorphous carbon contained in the rCF bundle is separated from the carbon fibers in the process of using the rCF bundle as a raw material for CFRP, etc., and is mixed into the compound resin. However, since the mixed amorphous carbon has a higher chemical stability than the compound resin, it has almost no effect on the mechanical properties of CFRP, etc. The presence or absence of amorphous carbon can be confirmed, for example, using a scanning electron microscope.

[0020] The average fiber length of the carbon fibers constituting the rCF bundle is not particularly limited, but is preferably, for example, 6 mm to 100 mm. If the average fiber length of the carbon fibers is less than 6 mm, the carbon fibers are too short, and the mechanical properties of the CFRP molded body obtained using the rCF bundle may not be sufficiently improved. Therefore, the average fiber length of the carbon fibers is preferably 6 mm or more, more preferably 8 mm or more, even more preferably 10 mm or more, and particularly preferably 25 mm or more. However, if the average fiber length of the carbon fibers is too long, the handling properties may be deteriorated, making it difficult to supply the rCF bundle composition according to the present invention to a molding machine, and making it difficult to use it as a recycled raw material. Therefore, the average fiber length of the carbon fibers is preferably 100 mm or less, more preferably 80 mm or less, and even more preferably 50 mm or less.

[0021] The number of carbon fibers constituting the rCF bundle is not particularly limited, but from the viewpoint of further improving the handleability of the rCF bundle, for example, it is preferably 500 to 480,000. The number of the carbon fibers is more preferably 1,000 or more, and even more preferably 5,000 or more. The number of the carbon fibers is more preferably 400,000 or less, and even more preferably 300,000 or less.

[0022] The rCF convergence composition according to the present invention contains a surface modifier in addition to the rCF convergence, and the surface modifier is characterized in that it has a second chemical functional group that shows chemical affinity with the first chemical functional group present on the surface of the carbon fiber contained in the rCF convergence. By containing the surface modifier, even if the rCF convergence is fed to a twin-screw extruder for example and used as a recycled raw material, fiber breakage of the carbon fiber can be prevented, so that dust generation can be suppressed and workability can be improved. In addition, by containing the surface modifier, wettability with the matrix resin kneaded when using the rCF convergence as a recycled raw material is improved, so that the mechanical properties of the produced molded body can be improved.

[0023] The formation of the rCF bundle is believed to be mainly due to the covalent bonds between C-C, as well as a small amount of ionic bonds and hydrogen bonds derived from carboxyl groups (-COOH groups). The amorphous carbon surface formed on the rCF surface has carboxyl groups (-COOH groups), but in the latest CFRP technology, PES resin (polyethersulfone resin) is added as an impact value improver to reduce the -SO n (n=2-4) and mainly have ionic bonding properties. The presence of such covalent bonds, ionic bonds, and hydrogen bonds is judged to have chemical affinity. The entire surface is not covered with these reactive groups, and the carbon skeleton of the rCF surface and amorphous carbon surface is exposed, so it is judged to have "no" chemical affinity. Therefore, the purpose of the present invention is to further improve the binding strength of the functional groups present on the amorphous carbon, and the activity of the surface of the rCF, etc. is improved according to the type of resin to be composited.

[0024] The first chemical functional group present on the surface of the carbon fiber is specifically at least one selected from a carboxyl group, an aldehyde group, and a carbonyl group, and is not limited to -SO n (n=2~4) may occur. -SO n It is derived from a thermoplastic resin (specifically, PES resin) that is added to the thermosetting matrix resin epoxy resin to improve impact resistance.

[0025] The second chemical functional group exhibiting chemical affinity with the first chemical functional group is specifically at least one selected from the group consisting of hydroxyl, epoxy, acryloyl, phenyl, acrylic, urethane, silanol, siloxane, ester, imide, nitrile, stearic acid, and maleic acid groups, and preferably contains at least one selected from the group consisting of hydroxyl, epoxy, acrylic, urethane, ester, imide, and nitrile groups, and more preferably contains at least one selected from the group consisting of hydroxyl, acrylic, imide, and nitrile groups.

[0026] Examples of the surface modifier include acrylic acid ester emulsion adhesives, water-soluble epoxy resins, and stearic acid or maleic acid used as an internal mold release agent for resins, as well as their salts. Acrylic acid ester emulsion adhesives are available, for example, from Toa Gosei Co., Ltd. Maleic anhydride is available, for example, from Mitsubishi Chemical Corporation.

[0027] The surface modifier must be contained in the range of 0.1 to 1% by mass when the entire rCF aggregate composition is taken as 100% by mass. If the amount of the surface modifier is less than 0.1% by mass, the amount of the surface modifier is too small, so the rCF aggregate is prone to fraying, and for example, when it is fed to an extrusion molding machine and used as a recycled raw material, dust generation cannot be suppressed, and the working environment cannot be improved. In addition, if the amount of the surface modifier is small, even if the rCF aggregate is used as a recycled raw material, the wettability with the matrix resin to be kneaded cannot be improved, and the mechanical properties of the molded body produced cannot be improved. Therefore, the amount of the surface modifier is 0.1% by mass or more, preferably 0.3% by mass or more, and more preferably 0.5% by mass or more. However, if the amount of the surface modifier exceeds 1% by mass, there is a disadvantage that the amount of the surface modifier is too large, so peeling during the drying and cutting process increases, and further the adhesive strength with the resin is impaired. Therefore, the amount of the surface modifier is 1% by mass or less, preferably 0.8% by mass or less, and more preferably 0.5% by mass or less.

[0028] The amount of surface modifier contained in the rCF aggregate composition can be measured by the difference (weight loss) between the mass after drying at 110°C for 1 hour and the mass at 250°C. To further improve accuracy and identify multiple components, the surface-treated fiber is washed with a solvent, dried under reduced pressure, and then quantified. In addition, it is identified by infrared absorption method, GPC, etc.

[0029] The rCF convergent composition according to the present invention has a residual carbon amount of 1 to 5% by mass when heated at 600°C for 60 minutes. The residual carbon amount means the amount of carbon contained in the rCF convergent composition, and the proportion of the amount of carbon that volatilizes at a temperature range of 600°C or less. When the residual carbon amount is 1% by mass or more, when the rCF convergent composition is kneaded into a matrix resin, very good fogging properties, dispersibility in the matrix resin, and good affinity state proceed extremely uniformly over the entire range, so that the kneadability of the rCF convergent with the matrix resin can be improved. The residual carbon amount is preferably 3% by mass or more, more preferably 3.5% by mass or more. On the other hand, when the residual carbon amount is 5% by mass or less, fogging proceeds smoothly during the kneading operation with the matrix resin, and the effect of appropriately suppressing scattering due to sudden fogging, that is, the formation of a dust state, is further enhanced, and an extremely excellent working environment can be maintained. The residual carbon amount is preferably 4.5% by mass or less, more preferably 4% by mass or less.

[0030] The amount of residual carbon can be calculated, for example, by measuring the weight change when the rCF aggregate composition is heated using a thermogravimetry (TG) device, and using the following formula based on the mass before and after heating at 600°C for 60 minutes. Residual carbon amount (mass%) = [mass before heating - mass after heating] / [mass before heating] x 100

[0031] The atmosphere in which the thermogravimetric measurement is performed is not particularly limited, and may be an air atmosphere. The amount of residual carbon can also be calculated by placing a sample in a crucible, heating it in the air, and measuring the amount of mass loss before and after heating.

[0032] If the raw material is prepreg scraps, the heating conditions may be 500°C x 60 minutes. This is because prepreg scraps have less adhesion to the matrix resin compared to CFRP scraps, the carbonization temperature of the matrix resin is lower, and the density of the carbonized product is also lower.

[0033] The rCF bundle composition according to the present invention contains the rCF bundle and the surface modifier, and may contain other components such as rubber components such as ethylene propylene rubber (EPDM). EPDM has good affinity with -SO3 and can improve adhesion to PP resin.

[0034] By using the rCF bundle composition obtained by the present invention, a non-crimp sheet of any width can be produced by arranging recycled carbon fiber bundles on a flat surface at their original size and joining them with a stitch sewing machine. In this non-crimp sheet, the recycled carbon fiber bundles are aligned in one direction. Therefore, by laminating the wide sheet with the carbon fiber bundle direction at angles of 0 degrees, ±45 degrees, and 90 degrees, it is possible to form the framework of a reinforcing structure using continuous rCF.

[0035] The above sheet is an rCF sheet in which the carbon fiber bundles are aligned in one direction, and the fibers do not overlap. The tow-shaped rCF bound with amorphous carbon are uniformly arranged in a flat surface, so that it can be easily impregnated with resin. Therefore, it is possible to manufacture a wide UD sheet impregnated with thermoplastic resin without disturbing the arrangement of the tows. By stacking the obtained sheets in a specified direction and applying a compression press, any 3D structure molded product can be obtained.

[0036] In addition, when the surface modifier is not contained, it is difficult to impregnate the thermoplastic resin, and therefore, for example, pressurization is required when producing the sheet. If pressurization is applied for a long period of time, collapse of the tow or displacement or collapse between the tow-like bundles occurs, resulting in a decrease in the strength of the sheet.

[0037] Next, a method for producing the recycled carbon fiber (rCF) bundle composition according to the present invention will be described.

[0038] The rCF convergence composition can be produced by a method including the steps of (1) heating a CFRP molded body to a temperature range of 400°C to 480°C in a heating furnace to obtain an rCF convergence body in which the carbon fibers are bundled into a tow shape with amorphous carbon that is substantially free of resin residues, and (2) contacting the obtained rCF convergence body with a liquid containing a surface modifier having a second chemical functional group that shows chemical affinity with the first chemical functional group present on the surface of the carbon fiber, and then drying the liquid. In the step of obtaining the rCF convergence (1), (1a) the CFRP molded body is heated in a temperature range of at least 300°C to 400°C under the flow of combustion gas in a heating furnace, and then (1b) it is necessary to hold the CFRP molded body in an atmosphere gas with an oxygen concentration of 16 to 18% by volume at a temperature range of 400°C to 480°C for at least 30 minutes.

[0039] The matrix resin (thermosetting resin) contained in the CFRP molded body is distilled and removed by heating with the combustion gas flowing in the heating furnace at a temperature range of at least 300°C to 400°C. By heating with the combustion gas flowing in the heating furnace, it is possible to sufficiently proceed with the distillation and removal of the matrix resin while minimizing the damage to the surface of the CFRP molded body caused by the oxygen potential in the air that constitutes the distillation atmosphere. However, this distillation and removal does not remove 100% of the matrix resin, but leaves behind an amount of amorphous carbon equivalent to the amount required to converge the carbon fibers into a tow shape.

[0040] After heating in the temperature range of 300° C. or more and 400° C. or less, the material is subsequently heated to a temperature range of 400° C. or more and 480° C. or less. In order to stabilize the amorphous carbon, the oxygen concentration in the atmospheric gas is controlled to a range of 16 to 18 volume %, and the retention time in this temperature range is set to at least 30 minutes.

[0041] In this way, by carefully controlling the heat treatment conditions of the CFRP molded body in two stages, the amount of residual carbon can be adjusted to fall within the above range.

[0042] The state changes that occur when a carbon fiber reinforced thermosetting resin (CFRP) molded body is heat treated are explained using the drawings. In addition, hatching and symbols may be omitted in each drawing for convenience, but in such cases, the specification and other drawings shall be referred to. In addition, the dimensions of various members in the drawings may differ from the actual dimensions because priority is given to contributing to understanding the features of the present invention.

[0043] Fig. 1 is a schematic diagram for explaining the state of a CFRP molded body when it is heat-treated. Fig. 1(a) shows the CFRP molded body before heat treatment, where A indicates the carbon fiber and B indicated by diagonal lines indicates the matrix resin.

[0044] The thermal decomposition of the matrix resin of the CFRP molding changes greatly depending on the heating conditions and the temperature range during heating. (b) in Figure 1 is a schematic diagram showing the state when heat-treated at 300°C to 400°C. The thermal decomposition of the matrix resin starts at around 300°C, but thermal decomposition gas is generated from inside the CFRP molding. When the inside is heated uniformly as shown in (b), the thermosetting resin softens once, and the decomposition gas generated inside is released to the surface. Here, the surface means not only the surface of the CFRP molding, but also the gaps of delamination (interlayer peeling occurs between the layers of the carbon fiber UD sheet or carbon fiber cloth) generated by the thermal decomposition process up to 300°C or between 300°C and 400°C, and the decomposition gas generated inside is released and released outside the system from the space of the delamination. If this reaction is continued, pores are continuously formed, and gas flow paths for the decomposition gas generated inside can be secured as open pores.

[0045] Figure 2(f) is a schematic diagram showing an enlarged view of the surface area surrounded by circle C for the CFRP molded product shown in Figure 1(b). As shown in (f), the pores on the surface are connected to the open pores inside the matrix, forming gas flow paths L. Therefore, during heat treatment, the amorphous carbon present around carbon fiber A is uniformly attacked by oxygen and removed, so damage to the surface of carbon fiber A is suppressed.

[0046] Fig. 1(c) is a schematic diagram showing the state when the temperature is further increased to 400°C to 480°C after Fig. 1(b) and heat treated. As shown in (c), when the temperature is increased to 400°C to 480°C, the open pores expand and the matrix resin B on the surface of the carbon fiber A is gasified leaving behind amorphous carbon α, which is a carbonization product.

[0047] On the other hand, a schematic diagram showing the state of the CFRP molded body shown in (a) of Figure 1 when it is heat-treated at 500°C is shown in (d) of Figure 1. When the temperature is raised to 500°C in a relatively short time with an emphasis on the recycling reaction time, as shown in (d), the matrix resin B of the CFRP molded body starts to decompose from the surface, gasifies and is released, but when the inside, which is heated later by external heating, reaches about 300°C, decomposition gas is generated. Some of the decomposition gas generated inside is released from the surface, but some remains inside and accumulates as voids. In addition, some of the matrix resin B present on the surface of the CFRP molded body is completely removed, and the carbon fiber A is exposed on the surface. Inside the matrix resin present between the carbon fibers A and in the parts close to the surface of the CFRP molded body, carbonization progresses and forms a layer, blocking gas release from the inside.

[0048] Figure 2(g) is a schematic diagram showing an enlarged view of the surface area enclosed in circle D for the CFRP molded product shown in Figure 1(d). As shown in (g), when heated to 500°C, the amorphous carbon on the surface is removed, turning into cotton-like carbon fibers and oxidizing the surface. The oxygen supplied from the surface of the CFRP molded product is blocked by the amorphous carbon layer, making it difficult for it to diffuse into the interior, leaving residual air bubbles p inside the CFRP molded product while the carbon fibers A surrounded by the amorphous carbon layer remain fixed in place.

[0049] FIG. 1(e) is a schematic diagram showing the state when the temperature is further increased to 600°C after FIG. 1(d) and heat-treated. As shown in FIG. 1(d), when the temperature is increased to 600°C, the matrix resin is carbonized and the carbonized layer is removed, followed by an amorphous carbon layer that does not contain pores or gas outlets, and furthermore, in the center, there are closed pores P that block the gas outlets, and some of them remain as resin with incomplete gas release. Conventionally, the resin was removed at a high temperature of 500°C or more, so that the carbon fiber A on the exposed surface was corroded by oxidation and could not reproduce its original mechanical performance. In addition, in addition to the amorphous carbon that could not be completely removed, there was also some undecomposed resin inside.

[0050] The method for producing the rCF convergent composition according to the present invention will be described in detail below. (1) A process for obtaining rCF convergence body In the process of obtaining the rCF bundle, the CFRP molded body is heated to a temperature range of 400°C or more and 480°C or less. By setting the heating temperature to a temperature range of 400°C or more and 480°C or less, an rCF bundle in which the carbon fibers are bundled into a tow shape with amorphous carbon that does not substantially contain resin residue can be obtained. In addition, the amount of residual carbon contained in the rCF bundle composition can be adjusted to a predetermined range. That is, if the heating temperature is lower than 400°C, heating is insufficient, amorphous carbon remains in excess, and the carbon fibers cannot be separated into an aggregate of single fibers. Therefore, the heating temperature is set to 400°C or more, preferably 410°C or more, and more preferably 420°C or more. However, if the heating temperature exceeds 480°C, excessive heating occurs, and the removal of amorphous carbon proceeds too much, the carbon fiber surface becomes an inactive smooth surface, and the bundle force is lost, and the workability when kneading with the matrix resin cannot be improved. In addition, the uniformity of the amorphous carbon removal cannot be maintained, the wettability with the matrix resin necessary for obtaining CFRP, etc. deteriorates, and an rCF aggregate with stable physical properties cannot be obtained. Therefore, the heating temperature is set to 480°C or less, preferably 470°C or less, and more preferably 460°C or less.

[0051] (1a) At least 300°C to 400°C When heating a CFRP molded body to a temperature range of 400° C. or higher and 480° C. or lower, the body is heated under flowing combustion gas in a heating furnace at least in the temperature range of 300° C. or higher and 400° C. or lower. By heating the CFRP molded body with the combustion gas flowing, the CFRP molded body can be heated uniformly without burning.

[0052] The average flow velocity of the combustion gas in the heating furnace in the temperature range of at least 300°C to 400°C is preferably, for example, 0.1 m / sec or more. By setting the average flow velocity of the combustion gas to 0.1 m / sec or more, the temperature of the CFRP surface can be easily controlled, so that the CFRP can be heated uniformly without uneven heating. The average flow velocity of the combustion gas is more preferably 0.5 m / sec or more, and even more preferably 1 m / sec or more. The average flow velocity of the combustion gas in the heating furnace is preferably large, and the larger the average flow velocity, the larger the surface diffusion velocity from the surface of the CFRP molded body, and the higher the internal diffusion rate and thermal diffusion rate, so that the decomposition rate of the thermosetting resin and the carbonization rate after decomposition can be increased. There is no particular limit to the upper limit of the average flow velocity of the combustion gas, but if the average flow velocity becomes too large, the CFRP molded body may be scattered depending on the mass of the CFRP molded body charged in the heating furnace. Therefore, the average flow velocity of the combustion gas is preferably 10 m / sec or less, more preferably 9 m / sec or less, and even more preferably 8 m / sec or less. The flow velocity of the combustion gas in the heating furnace can be controlled by providing a blower in the heating furnace, and can be measured by providing a gas flow meter in the heating furnace.

[0053] The oxygen concentration in the atmospheric gas when heating at a temperature range of at least 300°C or more and 400°C or less is not particularly limited, but is preferably 16 to 18% by volume, for example. If the oxygen concentration is below 16% by volume, the thermal decomposition rate constant drops drastically even at the same treatment temperature, and not only is sufficient thermal decomposition not performed, but undecomposed resin is mixed into the exhaust gas, becomes soot-like or tar-like, and accumulates on the pipe wall of the exhaust system, and the oxidation catalyst that normally oxidizes the hydrocarbon gas may be poisoned and lose activity. If the oxygen concentration exceeds 18% by volume, the internal diffusion rate of oxygen increases and the amount of heat generated inside increases, but the diffusion rate of the heat generated by oxidation inside cannot be increased, and the arrival of the heat generated by oxidation to the surface is delayed and it cannot be removed from the surface by a high-speed heat flow, so the internal heat generation cannot be controlled and may eventually become in a combustion state.

[0054] The oxygen concentration in the atmospheric gas at least in the temperature range of 300° C. or higher and 400° C. or lower is preferably controlled by mixing preheated air into the atmospheric gas flow in the heating furnace.

[0055] The oxygen concentration in the atmospheric gas when the CFRP molded body is heated from room temperature to 300°C is not particularly limited, but for example, the oxygen concentration is preferably controlled in the range of 13 to 19 volume%. By setting the oxygen concentration to 13 volume% or more, heating can be performed without discharging incomplete combustion gas. The oxygen concentration is more preferably 14 volume% or more, and even more preferably 15 volume% or more. However, if the oxygen concentration exceeds 19 volume%, the oxygen becomes excessive, which may cause uneven combustion or explosion in the heating furnace. Therefore, the oxygen concentration is preferably 19 volume% or less, more preferably 18 volume% or less, and even more preferably 17 volume% or less.

[0056] It is preferable to heat the CFRP molded body at least in the temperature range of 300°C or more and 400°C or less until the decomposition reaction of the thermosetting resin is completed. If the CFRP molded body is heated to 400°C or more without completing the decomposition reaction, oxidation of the CFRP molded body occurs suddenly, making it difficult to control the temperature, and white smoke and unpleasant odors may be generated, resulting in a poor working environment. In addition, the temperature of the CFRP molded body may rise suddenly, and the gas generated inside the CFRP molded body may not be sufficiently released outside the molded body, which may cause an explosion. In addition, the sudden oxidation may cause the CFRP molded body to become flocculent, making it impossible to form a tow shape.

[0057] The end of the decomposition reaction can be determined by observing whether or not smoke is emitted from the CFRP molded body, and the end of the decomposition reaction can be determined when smoke ceases. When the decomposition reaction has ended, it is preferable to confirm that no unpleasant odor is being generated. In addition, it is preferable to measure the gas concentration (e.g., oxygen concentration) in the atmospheric gas in the heating furnace and in the path for discharging exhaust gas from the heating furnace and to confirm that the gas concentration has stabilized.

[0058] The holding time in the temperature range of at least 300°C to 400°C must be the time required for the decomposition reaction of the thermosetting resin to be completed, and is, for example, preferably 1 hour or more and 5 hours or less. The holding time means the residence time in the temperature range of at least 300°C to 400°C, and refers to the time from when the temperature reaches 300°C to when the temperature reaches 400°C during the temperature rise process.

[0059] (1b) Temperature range: 400°C or higher and 480°C or lower After it is confirmed that the decomposition reaction of the CFRP molded body has ceased in the temperature range of 300° C. or more and 400° C. or less, the body is heated to a temperature range of 400° C. or more and 480° C. or less. By heating to a temperature range of 400° C. or more and 480° C. or less, a bundle in which the carbon fibers are bundled into a tow shape with amorphous carbon that is substantially free of resin residues can be obtained. The amorphous carbon preferably does not contain resin residues.

[0060] Heating in the temperature range of 400°C or more and 480°C or less must be performed in an atmosphere gas with an oxygen concentration of 16 to 18% by volume. If the oxygen concentration is below 16% by volume, amorphous carbon is difficult to generate, so the carbon fibers cannot be converged into a tow shape. In addition, the amount of residual carbon becomes excessive, so the workability of kneading with the matrix resin cannot be improved. In addition, the physical properties of the molded body cannot be stabilized. Furthermore, it takes time to generate decomposition gas, and the voids generated after decomposition become closed pores, which reduces the thermal decomposition rate and generates a heterogeneous phase. Therefore, the oxygen concentration is 16% by volume or more, preferably 16.3% by volume or more, and more preferably 16.5% by volume or more. However, if the oxygen concentration exceeds 18% by volume, the decomposition rate of the thermosetting resin increases, and part of it becomes in a burnt state and is oxidized and removed without generating amorphous carbon, so the carbon fibers cannot be converged into a uniform tow shape, and a flocculent and lumpy state coexist. In addition, the amount of residual carbon becomes too small, so that the workability of kneading with the matrix resin cannot be improved. In addition, the physical properties of the molded body cannot be stabilized. Therefore, the oxygen concentration is set to 18% by volume or less, preferably 17.8% by volume or less, and more preferably 17.5% by volume or less. The oxygen concentration in the atmosphere inside the heating furnace may be measured with an oxygen concentration meter.

[0061] The holding time in the temperature range of 400°C or more and 480°C or less is at least 30 minutes. By holding in this temperature range for at least 30 minutes, the amount of amorphous carbon that bonds the carbon fibers of the rCF bundle can be appropriately adjusted, and the amount of residual carbon can be adjusted to an appropriate range, so that the bundle can be precisely adjusted to a desired hardness. In addition, the workability of kneading with the matrix resin can be improved. In addition, the physical properties of the molded body can be stabilized. If the holding time is less than 30 minutes, the amount of amorphous carbon increases and the amount of residual carbon becomes excessive, so that the carbon fibers are firmly bonded to each other in a mass. As a result, it becomes difficult to stably measure the rCF bundle and also difficult to stably supply it to the extruder, so that it becomes difficult to use the rCF bundle as a raw material for recycling. Therefore, the holding time is 30 minutes or more, preferably 60 minutes or more, more preferably 90 minutes or more. The upper limit of the holding time is not particularly limited, but from the viewpoint of productivity, it is preferably, for example, 180 minutes or less, more preferably 150 minutes or less, and even more preferably 120 minutes or less. The above-mentioned holding time means the residence time in the temperature range of 400°C or more and 480°C or less, and means the time from when 400°C is reached to when 480°C is reached during the temperature increase process.

[0062] In the temperature range of 400°C or more and 480°C or less, the combustion gas in the heating furnace does not have to be made to flow, but it is preferable to make it flow. By heating under flowing combustion gas, uneven heating can be suppressed and the CFRP molded body can be heated uniformly. When the combustion gas in the heating furnace is made to flow in the temperature range of 400°C or more and 480°C or less, the average flow velocity of the combustion gas may be slower or faster than the average flow velocity of the combustion gas when heating in the above-mentioned temperature range of 300°C or more and 400°C or less, or may be the same.

[0063] The heating may be performed in the presence of pyrolysis gas (resin monomer, pyrolysis hydrocarbon, etc.) derived from the CFRP molded body, or in the presence of CO2 resulting from the reaction of the pyrolysis gas with oxygen and combustion. Furthermore, the heating may be performed while mixing these gases with an oxygen-containing gas. By mixing the oxygen-containing gas, the oxygen concentration in the atmospheric gas can be controlled. By slightly increasing the oxygen concentration and circulating the atmospheric gas, the pyrolysis of the resin and the oxidation reaction of the pyrolysis gas can be promoted without significantly changing the chemical equilibrium state, and as a result, the matrix resin can be converted into amorphous carbon. In addition, by slowly proceeding with the reaction, the decomposition gas with an odor can be introduced, for example, into a combustion chamber, completely combusted, and used as a heat source, while a part of it can be recirculated to a carbon fiber recovery furnace as a combustion gas that requires almost no additional exhaust gas treatment, and the rest can be released outside the system through a deodorizing device.

[0064] The oxygen-containing gas to be mixed may be, for example, air, oxygen gas, an inert gas containing oxygen gas, etc. The inert gas may be, for example, nitrogen gas.

[0065] After being heated and held in the temperature range of 400° C. or more and 480° C. or less, it is cooled to 300° C. or less. There are no particular limitations on the oxygen concentration in the atmospheric gas during cooling, and cooling may be performed in the air, for example.

[0066] When repeatedly treating in the same heating furnace, for example, the heat source is shut off at the end of the treatment, the atmospheric gas is continued to circulate, the rCF aggregate is removed when the temperature is below 400°C, and then new CFRP molded bodies are loaded into the heating furnace that has been cooled to approximately 300°C. It is then possible to start the next batch treatment after confirming that the temperature of the CFRP molded bodies has stabilized at 300°C or less.

[0067] The CFRP molded body may be a used recovered product or a product that has been recovered as a non-standard product. It may also be prepreg scraps generated during manufacturing, trimmings, or the like. It is preferable to clearly separate such CFRP molded bodies according to their source and strictly manage their traceability. In addition, when specifying the recycling grade of a product, it is preferable to limit it to products recovered from the market and clearly distinguish it from recycled products recovered in the process. When, for example, a plating layer or a coating layer is formed on the surface of the CFRP molded body, it is preferable to remove the plating layer or coating layer in advance before heating.

[0068] (2) A step of contacting the surface with a liquid containing a surface modifier and then drying the liquid. The recycled carbon fiber bundle composition of the present invention can be produced by contacting the rCF bundle obtained in (1) above with a liquid containing a surface modifier having a second chemical functional group that exhibits chemical affinity with the first chemical functional group present on the surface of the carbon fiber, and then drying.

[0069] The liquid containing the surface modifier may be the surface treatment agent itself, or may be a liquid in which the surface treatment agent is dispersed or dissolved in water or an organic solvent. Examples of the solvent used to disperse or dissolve the surface treatment agent include ethyl acetate, MEK, toluene, ethanol, IPA, methanol, and mixed solvents thereof. The concentration of the surface treatment agent contained in the liquid in which the surface treatment agent is dispersed or dissolved is preferably, for example, 0.01 to 0.0001 mass%.

[0070] The method of contacting the rCF convergent with the surface modifier-containing liquid is not particularly limited, and examples include a method of immersing the rCF convergent removed from the heating furnace in the surface modifier-containing liquid, or a method of spraying the surface modifier-containing liquid onto the rCF convergent.

[0071] After the rCF aggregate is brought into contact with the liquid containing the surface modifier, it is dried. The drying temperature is preferably, for example, 110°C to 180°C. By setting the drying temperature at 110°C or higher, the amount of water or residual solvent can be reduced. The drying temperature is more preferably 115°C or higher, and even more preferably 120°C or higher. However, if the drying temperature exceeds 180°C, a part of the surface modifier may be volatilized or thermally decomposed in the air, and the remaining amount of the surface modifier may become too small. Therefore, the drying temperature is preferably 160°C or lower, more preferably 135°C or lower, and even more preferably 130°C or lower.

[0072] The drying time is preferably, for example, 60 to 180 minutes, with the rCF aggregate uniformly spread on a drying rack to a thickness of 100 mm.

[0073] The rCF aggregate composition thus obtained can be suitably used as a raw material for CFRP molded bodies or CFRTP molded bodies. The rCF aggregate composition is fed to an extrusion molding machine, mixed with a separately fed thermosetting resin or thermoplastic resin, and molded under known conditions to produce a CFRP molded body or a CFRTP molded body.

[0074] The rCF bundle composition can be suitably used in particular for side feeding from a side feeder of an extruder.

[0075] The type of the extruder is not particularly limited, and examples thereof include a single screw extruder and a multi-screw extruder. The single screw extruder is a single screw extruder, and the multi-screw extruder is, for example, a twin screw extruder or a composite machine of a single screw and a twin screw.

[0076] This application claims the benefit of priority based on Japanese Patent Application No. 2021-090412, filed on May 28, 2021. The entire contents of the specification of Japanese Patent Application No. 2021-090412 are incorporated by reference into this application.

[0077] The present invention will be described in more detail below with reference to examples. However, the present invention is not limited to the following examples, and it is of course possible to carry out the invention with modifications within the scope of the above and below-described aims, and all of these modifications are included in the technical scope of the present invention. EXAMPLES

[0078] [Experiment 1] In experiment 1, a used compressed natural gas tank (CNG tank) was used as a carbon fiber reinforced thermosetting resin molded body by cutting off the dome parts on both ends to make it cylindrical and removing the aluminum container inside. The cylindrical CNG tank had a diameter of about 40 cm, a length of about 152 cm, and a thickness of about 1 cm. It is also possible to cut off only the cap parts on both ends and cut the cylindrical part linearly from the dome part before putting it into the furnace. In that case, the aluminum liner is collected as it is, and the rCF separated in half is collected in a stacked state, which allows the collection of rCF with longer fiber length, making it easier to cut later.

[0079] A cylindrical CNG tank was cut into four pieces so that the circumferential length was equal, and the tank was divided. The thermoplastic resin constituting the cylindrical CNG tank was epoxy resin. The four divided CNG tanks were placed in a heating furnace and held at 300°C to 400°C for 90 minutes to carbonize the resin, and then heated to a temperature range of 400°C to 470°C. The four divided CNG tanks were not stacked on top of each other, but were arranged with gaps between them so that the combustion gas in the heating furnace would come into uniform contact with the surface of the CNG tank. In other words, the CNG tank was arranged so that its longitudinal direction and the flow direction of the atmospheric gas were the same (parallel).

[0080] The lid of the heating furnace was closed, and a heat-resistant fan installed in the exhaust section of the heating furnace was operated to circulate the combustion gas in the heating furnace from the time when the temperature in the heating furnace reached 300°C to the end of heating. The average flow velocity of the combustion gas in the heating furnace was 0.05 m / sec. In addition, air was taken in from a variable speed blower installed in the heating furnace, and the oxygen concentration in the atmosphere gas in the heating furnace was measured with a zirconia type oxygen sensor and controlled to 18 volume %. The oxygen concentration in the atmosphere gas in the heating furnace was 18 volume % from the time when the temperature in the heating furnace reached 300°C to 400°C, and 16 volume % from 400°C to the end of heating. The retention time in the section from the time when the temperature in the heating furnace reached 300°C to 400°C was 1.5 hours. The average temperature increase rate in the section from the time when the temperature in the heating furnace reached 300°C to 400°C was 50°C / min. The decomposition state of the CFRP molded body was confirmed in advance just before reaching 400 ° C in the experimental furnace, and if the decomposition reaction was terminated, the heating was continued and the temperature was raised. The termination of the decomposition reaction was confirmed by observing the presence or absence of smoke generation along with the confirmation in the experimental furnace, and it was determined that the decomposition reaction was terminated when smoke generation was not generated. In addition, the presence or absence of an abnormal odor was also observed, and it was confirmed that an abnormal odor was not generated. After confirming the termination of the decomposition reaction, the heating temperature was set to 470 ° C and heated. The temperature range of 400 ° C or more and 470 ° C or less was maintained for 30 minutes. After the heating was completed, it was cooled and an rCF convergence body was obtained. The obtained rCF convergence body was converged into a tow shape with amorphous carbon derived from a thermosetting resin. The mass ratio of amorphous carbon to the mass of the rCF convergence body was 5%, the potential hydrogen content of the rCF convergence body was 8000 ppm, and it did not substantially contain resin residue.

[0081] The carbon fibers contained in the rCF bundle had a carboxyl group (-COOH group) as the first chemical functional group on their surfaces. The average fiber length of the carbon fibers constituting the rCF bundle was 2000 mm, and the average number of carbon fibers was 24000.

[0082] Next, the obtained rCF bundle was brought into contact with a liquid containing a surface modifier, and then dried to produce a recycled carbon fiber bundle composition. An "acrylic acid ester emulsion adhesive" manufactured by Toa Gosei Co., Ltd. was prepared as a surface modifier, and water was added to the "acrylic acid ester emulsion adhesive" to prepare a liquid containing the surface modifier in which the solid content of the acrylic acid ester emulsion adhesive was 2 mass%. The surface modifier contains a hydroxyl group (-OH group) as a second chemical functional group, and this second chemical functional group shows chemical affinity with a carboxyl group (-COOH group), which is a first chemical functional group present on the surface of the carbon fiber.

[0083] The rCF convergent was immersed in the liquid containing the surface modifier for 5 minutes to bring the rCF convergent into contact with the liquid containing the surface modifier. After the contact, the rCF convergent was lightly squeezed with a roller and then dried. The drying was performed at 120°C. The surface modifier was 0.3% by mass when the entirety of the obtained rCF convergent composition was taken as 100% by mass. The obtained rCF convergent composition was placed in a crucible with a lid and heated at 600°C for 60 minutes, and the amount of residual carbon was measured. As a result, when the entirety of the recycled carbon fiber convergent composition was taken as 100% by mass, the amount of residual carbon was 1.2% by mass.

[0084] After drying, the carbon fibers were cut to a length of about 25 mm. Because there was almost no dust generated when cutting the rCF aggregate composition, the cutting speed could be increased to 90% or more of the cutting speed of the cutter. In addition, the supply amount of the rCF aggregate composition could be increased, so that the cutting amount per unit time could be increased to 25 kg / hour (200 mm wide cutter).

[0085] Next, the recycled carbon fiber bundle composition cut to 25 mm was fed from the side feeder of a twin-screw extruder, kneaded with 6 nylon resin (1013B manufactured by Ube Industries) fed from the main feeder, and formed into strands (extruded noodle-like) that were then pelletized to 6 mm length using a pelletizer. Pellets containing 40% by mass of the recycled carbon fiber bundle composition per 100 parts by mass of 6 nylon were used to produce molded bodies using a 180-ton injection molding machine manufactured by Nissei Plastics.

[0086] The recycled carbon fiber bundle composition did not generate dust even when fed from a side feeder, and no deterioration of the working environment was observed. In addition, the surface-treated recycled carbon fiber bundle composition did not lose its holding strength even in the side feeder heated by the resin temperature because the amorphous carbon bundle material functioned, and it was quickly kneaded with 6 nylon resin, at which point a uniform defibrated state was obtained, and the workability was good.

[0087] Next, the mechanical properties of the obtained molded body were evaluated. The mechanical properties were measured for tensile breaking strength and tensile breaking elongation based on JIS K7161-2 / 1A / 5. As a result, the tensile breaking strength was 252.2 MPa and the tensile breaking elongation was 1.66%. In addition, the Charpy impact strength was measured at 23°C with a notch based on JIS K7111-1 / 1eA. As a result, it was 9 kJ / m 2 It was.

[0088] [Experiment 2] In experiment 1, the obtained recycled carbon fiber bundle composition was mixed with PES resin, and a molded body was produced in which the thermoplastic resin was reinforced using the recycled carbon fiber bundle. A twin-screw extruder was used to produce the molded body, and the recycled carbon fiber bundle composition was fed from a side feeder. The recycled carbon fiber bundle composition was mixed at 55 mass% with respect to 100 mass parts of thermoplastic resin to produce a molded body. The recycled carbon fiber bundle composition did not generate dust even when fed from the side feeder, and no deterioration of the working environment was observed. In addition, the recycled carbon fiber bundle composition was quickly mixed with the PES resin, and the workability was good. An extrusion port (die) with a thickness of 7 mm and a width of 90 mm was attached to the tip of the twin-screw extruder, and a plate-shaped molded body was produced by extrusion. The specific gravity of the obtained plate-shaped molded body was 1.34, which was almost equal to the theoretical value. The obtained plate-shaped molded body was inserted into a mold and hot-press molded to obtain a molded product in the shape of a smartphone. The mechanical properties of the obtained molded product were evaluated, and it was found that the bending strength was comparable to that of magnesium die casting, and the bending modulus exceeded 40 GPa.

[0089] [Experiment 3] The plate-shaped product obtained in Experiment 2, having a thickness of 7 mm and a width of 90 mm, was inserted directly into a heated roll and stretched to a thickness of 0.5 mm to produce a strip-shaped product having a width of approximately 20 mm.

[0090] [Experiment 4] In experiment 4, a molded body was produced without using a surface modifier in the above experiment 1. That is, in the above experiment 1, after heating, the rCF bundle obtained by cooling was mixed with a thermoplastic resin to produce a fiber-reinforced molded body. The rCF bundle obtained by cooling was cut so that the length of the carbon fiber was about 25 mm, but since dust was generated during cutting, it was only possible to cut at a speed of about 60% of the cutting speed of the cutter. In addition, since the supply amount of the rCF bundle composition could not be increased, the cutting amount per unit time was only 5 kg / hour. Nylon 6 resin was used as the thermoplastic resin. A twin-screw extruder was used to produce the molded body, and the rCF bundle was supplied from a side feeder. The rCF bundle was mixed with 30 mass% of the thermosetting resin with 100 mass parts to produce a molded body. When the rCF bundle was supplied from the side feeder, more dust was generated than in the above experiment 1, and the working environment was slightly worse than in the above experiment 1. In addition, compared to the above experiment 1, the rCF bundle had slightly worse kneadability with the nylon 6 resin.

[0091] Next, the mechanical properties of the obtained molded body were evaluated in the same manner as in Experiment 1. As a result, the tensile breaking strength was 233 MPa, the tensile breaking elongation was 1.3%, and the Charpy impact strength was 6.8 kJ / m 2 It was.

Claims

1. A recycled carbon fiber bundle extracted from a carbon fiber reinforced thermosetting resin molding; a surface modifier having a chemical functional group (hereinafter referred to as a second chemical functional group) that exhibits chemical affinity with a chemical functional group (hereinafter referred to as a first chemical functional group) present on the surface of the carbon fiber; The recycled carbon fiber bundle composition contains the following: The recycled carbon fiber bundle is formed by bundling carbon fibers into a tow shape using amorphous carbon that is substantially free of resin residues, The recycled carbon fiber bundle composition contains 0.1 to 0.8% by mass of the surface modifier when the entire recycled carbon fiber bundle composition is taken as 100% by mass, and The recycled carbon fiber bundle composition has a residual carbon amount of 1 to 5 mass % when the recycled carbon fiber bundle composition is heated under conditions of 600° C. for 60 minutes and measured.

2. the first chemical functional group is at least one selected from a carboxyl group, an aldehyde group, and a carbonyl group; 2. The recycled carbon fiber bundle composition according to claim 1, wherein the second chemical functional group is at least one selected from the group consisting of a hydroxyl group, an epoxy group, an acryloyl group, a phenyl group, an acryl group, a urethane group, a silanol group, a siloxane group, an ester group, an imide group, a nitrile group, a stearic acid group, and a maleic acid group.

3. A sheet formed from the recycled carbon fiber bundle composition according to claim 1 or 2.

4. A method for producing the recycled carbon fiber bundle composition according to claim 1 or 2, comprising the steps of: a step of heating the carbon fiber reinforced thermosetting resin molded body in a heating furnace to a temperature in the range of 400° C. or more and 480° C. or less to obtain a recycled carbon fiber bundle in which the carbon fibers are bundled into a tow shape with amorphous carbon that is substantially free of resin residue; and contacting the obtained recycled carbon fiber bundle with a liquid containing a surface modifier having a second chemical functional group that exhibits chemical affinity with a first chemical functional group present on the surface of the carbon fiber, followed by drying. In the step of obtaining the recycled carbon fiber bundle, the carbon fiber reinforced thermosetting resin molded body is heated in a temperature range of at least 300°C to 400°C under a flow of combustion gas in a heating furnace, and then is held in an atmospheric gas having an oxygen concentration of 16 to 17.8 volume % in a temperature range of 400°C to 480°C for at least 30 minutes.

5. The method according to claim 4, wherein the average flow velocity of the combustion gas in the heating furnace is 0.1 to 10 m / sec.

6. 6. The method according to claim 4, wherein the heating in the temperature range of 300° C. or more and 400° C. or less is continued until smoke generation from the carbon fiber reinforced thermosetting resin molded body ceases.

Citation Information

Patent Citations

  • Method for treating carbon fiber reinforced plastic

    JP1994099160A

  • Production of carbon short fiber

    JP1999050338A

  • Carbon fiber strand for thermoplastic resin reinforcement

    JP2006124852A

  • Method for recycling fiber-reinforced plastic

    JP2009138143A

  • Method for producing nonwoven fabric and method for producing composite material

    JP2014196584A